2018
DOI: 10.4066/biomedicalresearch.29-18-177
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of physical activity on depression, anxiety, stress and quality of life of patients on hemodialysis

Abstract: Individuals diagnosed with Chronic Kidney Disease (CKD) usually develop psychiatric complications as the dialysis procedure causes changes in the physical health and social life. Though the literature supports beneficial effects of exercise programmes in dialysis patients, the implementation of exercise as a part of clinical care is very less. Hence, the present study was undertaken to provide further evidence for the effectiveness of physical activity depression, anxiety, stress and quality of life of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Furthermore, providing physical activity on patients undergoing hemodialysis, which consists of elbow flexion/extension, forearm supination/pronation, wrist circumduction, fingers flexion/extension, ankle rotation, toes flexion, extension and hyper extension, were found to be significantly reducing the levels of depression and improving the quality of their life. However, the results recommends to support these finding with other experimental studies using different approach of physical exercises [38].…”
Section: Physical Exercises and Psychological Status Among Patients Usupporting
confidence: 56%
See 2 more Smart Citations
“…Furthermore, providing physical activity on patients undergoing hemodialysis, which consists of elbow flexion/extension, forearm supination/pronation, wrist circumduction, fingers flexion/extension, ankle rotation, toes flexion, extension and hyper extension, were found to be significantly reducing the levels of depression and improving the quality of their life. However, the results recommends to support these finding with other experimental studies using different approach of physical exercises [38].…”
Section: Physical Exercises and Psychological Status Among Patients Usupporting
confidence: 56%
“…The prevalence rate of anxiety ranged from 21% to 48% [38]. Moreover, the higher levels of anxiety were significantly correlated with females, increased patients' age, low level of education, retirement status, poor financial situation, and co-morbidities [39].…”
Section: Physical Exercises and Psychological Status Among Patients Umentioning
confidence: 97%
See 1 more Smart Citation
“…Instead, exercise therapy has been considered as an appropriate option to reduce depression in hemodialysis patients [15][16][17][18][19]. Scientists have demonstrated that the release of beta-endorphins during exercise plays an important role in the construction of hippocampal neurons and reduce depression [20]. In addition, exercise also reduces depression by changing the growth hormones and cortisol hormones [20].…”
Section: Introductionmentioning
confidence: 99%
“…all the collected samples have phosphate concentration ranging from 0.00 to 0.009 mg/l. all the water samples of phosphate concentration are under the limit of [20] USPHS as 0.1 mg/l. [21] Prasanna et al 2010, studied physicchemical properties of water collected from Dharma Estuary and analysed the phosphate content and values were found ranged between 0.04 to 1.15 mg/l.…”
Section: Phosphatementioning
confidence: 99%